Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan Perkebunan Kelapa Sawit - Merliyana, Reny Dany; Windi Ariesti Anggraeni (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This research aims to determine how the influence of Corporate Social Responsibility (CSR) Disclosure on Financial Performance represented by Return on Asset (ROA) and Return on Equity (ROE). This study uses secondary data on Palm Oil Sub-Sector companies for 5 years (2017-2021) obtained from www.idx.co.id and the company's official website in the form of Annual Reports and Sustainability Reports. Through purposive sampling method as a sampling technique, 15 (fifteen) oil palm plantation sub-sector companies were obtained. CSR disclosure indicators are guided by the GRI Index with 30 indicators. The hypothesis testing method used is panel data regression analysis using the eviews program version 9. The results of the study through the REM model test analysis show that CSR disclosure has no effect on ROA where the probability is 0.3080 (prob> 0.05), the correlation between variables is weak at 1.4%, and the FEM model test that CSR disclosure has no effect on ROE where the probability is 0.5953 (prob> 0.05), the correlation between variables is also quiet weak at 43%. This means that the disclosure of Corporate Social Responsibility implemented by palm oil sub-sector companies during the period of this study does not directly affect the financial performance of these companies.